Pedagogika i Edukacja wobec Kolizji Etosów - Kwieciński, Zbigniew (Rocznik Pedagogiczny, 2019)
The essay proposes a way to search for common educational goals in a situation marked by deep political and worldview-related divisions in Polish society. It recalls Kazimierz Sośnicki’s concept of the “collision of ethoses” conceived in the 1930s, and the need to overcome shallow ‘ceremonial- ism’ in order to move towards a deeper experience of values, both spiritually and through altruistic actions.